2001
DOI: 10.1046/j.1365-2648.2001.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Equal opportunities policies and nursing employment within the British National Health Service

Abstract: This paper discusses the continuing failure of equal opportunities policies to have a sustained impact on the experiences of minority ethnic nurses and discusses a number of reasons for the lack of progress of such policies. It examines the reasons why health care organizations might adopt equal opportunities policies and the pragmatic reasons why implementation has been both slow and patchy. It goes on to consider the concepts of managing diversity and ethnic managerialism as new tools to theorize equal oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…A qualitative study conducted [23] showed that African nurses had some difficulties in adapting and gaining promotion in the NHS in the UK and the authors appeared to be suggesting that African nurses' racial features were contributory factors and the findings from this present research concur with that of a similar study [24]. Given such differences in treatment, the analysis leaves open to question whether having substantive equal opportunity policies is improving outcomes for all overseas nurses.…”
Section: Discussionsupporting
confidence: 76%
“…A qualitative study conducted [23] showed that African nurses had some difficulties in adapting and gaining promotion in the NHS in the UK and the authors appeared to be suggesting that African nurses' racial features were contributory factors and the findings from this present research concur with that of a similar study [24]. Given such differences in treatment, the analysis leaves open to question whether having substantive equal opportunity policies is improving outcomes for all overseas nurses.…”
Section: Discussionsupporting
confidence: 76%
“…Th is diversity has brought some positive eff ects to the NHS, not the least of which is the relief on the chronic nurse shortage that characterized the NHS throughout the 1980s. However, these overseas nurses have frequently cited racism and harassment as distressing experiences in their working life in NHS hospitals as well as in the private sector in terms of career opportunities (Alexis & Vydelingum, 2004;Allan & Larsen, 2003;Allan, Larsen, Bryan, & Smith, 2005;Archibong & Darr, 2010;Beishon, Virdee, & Hagell, 1995;Culley, 2000;Herbert, Datta, Evans, May, McIlwaine, & Wills, 2006;Larsen, 2007;Lemos & Crane, 2001;Likupe, 2006;Nichols & Campbell, 2010;Royal College of Nursing, 2008;Shields & Wheatley Price, 2002;Taylor, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Published literature (Alexis et al, 2003;Archibong et al, 2007;Ashraf & Archibong, 2010;Culley, 2001;Esmail, 2007) suggests that BME staff working in NHS organizations face many challenges in progressing to senior positions, including the lack of mentors or role models. BME staff often experience noninclusion from informal networks, stereotyping, and lack of important leadership and line management experience, as well as personal commitments and family responsibilities (Esmail, 2007).…”
Section: Barriersmentioning
confidence: 99%
“…At the same time, some NHS organizations are attempting to implement equal opportunities policies and promote a "positive image" to recruit people from diverse backgrounds (Alexis et al, 2003). Evidence suggests, however, that there are inconsistencies in the implementation of equal opportunities, causing barriers for people especially from minority ethnic backgrounds to progress into leadership and management positions in health institutions Beishon, Virdee, & Hagell, 1995;Culley, 2001). In those organizations in which senior managers were unsuccessful in understanding equal opportunities policies clearly, resources for developing and training staff were not allocated (Esmail, 2007).…”
Section: Legal Framework and Employmentmentioning
confidence: 99%
See 1 more Smart Citation